Evaluation of Continuous Salt Recovery from Saline Solutions Using Fluidization with Inert Particles - Reyes-Salinas, A; Henriquez-Vargas, L; Pailahueque-Barahona, N (ELSEVIER, 2025)
Brine and saline water discharge from desalination plants back into the environment poses negative consequences as it disrupts the marine ecosystem by severely increasing the water salinity levels in the vicinity of the discharge area. This work presents and evaluates a continuous process for the drying of like effluents allowing to recover solid salt using fluidization technology. As process variables, the effect of air temperature between 50 and 70 degrees C, the flow of salt solutions between 3 and 4 l/h, with a concentration between 35 and 70 g/l, on the amount of solid salt recovered in a fluidized bed using inert particles were studied. Experimental results show the technical feasibility of dehydrating salt solutions in a fluidized bed, obtaining solid salt as a product with moisture contents around 1% with sizes under 50 mu m. In continuous operation, salt recovery between 40 and 70% was observed, with the highest recovery obtained at 70 degrees C. Of the factors studied, drying air temperature and salt solution flow rate were statistically significant. Simple mass and energy balances provide a good correlation for the water mass evaporation rate.